Tensile, Thermal And Uv-Resistance Properties Of Poly(Lactic Acid)/Zinc Oxide Treated Halloysite Nanotubes Nanocomposites - Lim, Keemi (2019)
The aim of this research is to prepare poly(lactic acid)/halloysite nanotube PLA/HNT nanocomposites (with and without zinc oxide (ZnO) treatment) with high photostability. ZnO treated HNT with optimum charge stability, structural and morphological properties were successfully fabricated via a solvent free technique. Thereafter, HNT-ZnO (1:2) (the optimum formulation) was incorporated into PLA, and the effects of ZnO treated HNT at various loadings (1, 3, 5, 7, 10 wt%) were evaluated on the mechanical, thermal and UV resistance properties with respect to PLA/HNT nanocomposites. PLA/HNT-3 shows a balance in tensile modulus, tensile strength and elongation at break. The thermal stability of both PLA/HNT-ZnO and PLA/HNT are higher than that of PLA. UV-Vis results demonstrated that addition of ZnO substantially enhanced the UV-blocking ability of PLA nanocomposites whilst maintaining moderate transparency in film. Upon exposure to accelerated weathering test for a period of 0, 30 and 60 days, PLA/HNT nanocomposites with ZnO treatment showed decreased in the yellowing index (YI) and not much change in colour of films was noted. The low YI values denote that the UV resistance was higher in PLA/HNT-ZnO films as compared to PLA/HNT. In addition, FTIR studies revealed the decrease in carbonyl index (ICO) values of PLA/HNT-ZnO at the initial stage of 30 days. This is associated that in presence of HNT-ZnO, the PLA nanocomposites are less susceptible to photodegradation, as less occurance of chain scission and lesser reduction in the molecular weight of PLA were discerned.